Terapi Remedial Untuk Meningkatkan Kemampuan Membaca Dan Menyimak Pada Anak Dengan Disabilitas Intelektua - Diyantari, Putu Ayu; Budisetyani, I Gusti Ayu Putu Wulan (Jurnal Psikologi Udayana, 2016)
The children with intellectual disability have characteristics, such as significant disability in functioning whether it is intellectually or adaptively which is realised through the ability of conceptual, social, and practice. This situation appears before the age of 18 yeears old.In educational level as Elementary School, children are often emphasized in order to have reading ability. If children in early educational level do not have reading ability, they will have difficulties in learning such kinds of subject on next level. Other than obtaining the reading practice at school, children also obtain such lesson as gathering a story. In this case, children should be able to comprehend the story, memorize the character of the story, and comprehend the background and plot of the story. The activities of reading and gathering a story for children who are classified into intellectual disability will have more difficulties rather than those children who do not have disabilities and have education in regular school. The researcher design the modification program for those children like this which is known by remedial therapy. Remedial therapy is a healing or improvement effort, an enhancement of someone’s intellectual to be normal or near normal (Mangunsong, 2009). This research was quantitative research which used Wilcoxon analysis. The data were collected through experiment method with pre-experiment design. The technique used to obtain the sample was purposive sampling. The subject of this research were the children who have intellectual disability, in amount of three children. The result of this research showed that the probability of reading ability was 0.028 (p)<0.05, while the probability of gathering a story was 0.027 (p)<0.05. It means that there were effects of remedial therapy toward reading ability and gathering a story on children’s intellectual disability. Key words: Remedial Therapy, The Abilities of Reading and Gathering a Story, Intellectual Disability.